Study of Visitor Activities in Public Spaces at Sudirman Square Lhokseumawe - Regina; Cut Azmah Fithri; Hendra Aiyub (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
Humans are dynamic, active and always on the move. Humans carry out various activities to fulfil their needs both physically, mentally and socially. These activities can be done anywhere, one of which is in the public space at Sudirman Field in Lhokseumawe. This research will focus on public spaces in Sudirman Square Lhokseumawe as a case study to examine visitor activities. This research aims to examine how visitor activities in public spaces in Lhokseumawe Sudirman Square. This research uses a qualitative method descriptive approach and uses the theory by John Gehl regarding activities in public spaces. This research concludes that Sudirman Field is a multifunctional field that has a variety of activities. These activities include need activities in the form of routine sports, trading and relaxing, choice activities in the form of optional sports, relaxing, children's playgrounds and social activities in the form of exhibitions, festivals, other major events, chatting with visitors and team sports. The intensity of activities that occur in Sudirman Square will increase during weekends and during major events such as exhibitions, fairs and festivals. However, this only happens on certain days or times. Sudirman Square is in accordance with Gehl's theory of applying the three types of activities in public space. Thus, it becomes a special attraction for the visitors. Thus, it becomes a special attraction for visitors because of the variety of activities that can be done.